Dentoalveolar trauma induced by intubation in urgent maxillofacial surgery: case report - Taysnara Ismaeley de ANDRADE; Kaiane Tavares PONTES; Francisco Rikilly de ARAÚJO; Joelma Silva de ANDRADE; José Eudes Protázio de OLIVEIRA (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Dental trauma is a common complication in general anesthesia, especially when using nasotracheal intubation during the classic laryngoscopy. Risk factors range from difficult intubation through difficult airways to occlusal changes in the patient, with incisors being widely affected by dental elements. Tooth avulsion is the most frequent type of trauma, followed by lateral dislocation and root fracture. Male patient, 39 years old, presented at the Emergency and Trauma Hospital in Caruaru/PE, a motorcycle accident victim with a bilateral jaw fracture. Given the need to fix fractures, the patient underwent a surgical procedure under general anesthesia. During laryngoscopy, heavy bleeding was observed in the oral cavity. After inspection, root fracture of lateral incisor and avulsion of right central incisor were noted. The avulsionated tooth was not found. An orthopedic image intensifier was used to locate the dental element in the thoracic region. However, it was not possible to determine its location. Therefore, an upper gastrointestinal (UGI) endoscopy was requested, and the dental element was in the digestive tract at the esophagus level. The tooth was removed, and the surgical procedure for osteosynthesis of bilateral mandible fracture was carried on. Dentoalveolar traumas induced by general anesthesia are frequent and require preventive measures since they can directly affect the patient's physical, economic, and medical conditions, along with anesthesiologists and maxillofacial surgeon's risk of receiving a civil lawsuit.